The difference in supine versus standing plain radiograph of the knee in patients with knee osteoarthritis - Musa, Abdullah Aqeel; Shamsuddin Perisamy, Rajeev; Low, Chooi Leng; Zulkifly, Ahmad Hafiz; Kow, Ren Yi (Malaysian Orthopaedic Association (MOA), 2025)
Introduction: Knee osteoarthritis is a degenerative jointdisease attributed to failure in joint repair process. Keyaspect of the diagnosis relies on thorough history, along withphysical examination and radiology findings. Theconventional weight-bearing plain radiograph remains thekey modality to determine the severity of the condition andhelps to plan the surgery. Nevertheless, not all patients canundergo weight-bearing plain radiographs, especially thosewho are wheelchair-bound or have severe deformities. Thepurpose of this study is to investigate whether a weight-bearing plain radiograph of the knee is essential in allpatients with knee osteoarthritis.Materials and methods: A prospective cohort study onpatients with knee osteoarthritis receiving treatment in asingle tertiary hospital was conducted. All patients consentedto participate in this study. Patients were assessedfunctionally with the Western Ontario and McMasterUniversities Osteoarthritis Index (WOMAC) andradiologically with plain radiographs. Patients weresubjected to undergo both supine and standing plainradiographs of the knee in the same setting for comparisonpurposes where measurement is done following patientfunctional outcome and radiological measurement for thepatient.Results: Our study shows that reduction in joint space ismore obvious in weight-bearing radiographs, however insevere or higher-grade osteoarthritis, a supine radiograph isadequate to diagnose knee osteoarthritisConclusion: Standing radiograph of the knee is preferred toa supine knee radiograph wherever possible due to theadditional value it brings, however, in certain patientconditions, a supine radiograph is still acceptable.